THE EFFECT OF TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL CULTURE AND EMPLOYMENT MOTIVATION ON THE MANAGERIAL PERFORMANCE THROUGH ORGANIZATIONAL CITIZENSHIP BEHAVIOR - T.A Hariyono T.A Hariyono (International Conferences SDGs 2030 Challenges and Solutions, 2030)
The purpose of this study is to analyze the influence of transformational leadership, organizational culture and work motivation on organizational citizenship behavior and managerial performance at PT. Cobra Direct Sale Indonesia. Analyzing the influence of organizational citizenship behavior on managerial performance at PT. Cobra Direct Sale Indonesia and analyzed the influence of transformational leadership, organizational culture and work motivation on managerial performance through organizational citizenship behavior at PT. Cobra Direct Sale Indonesia. Population in this research is manager of PT. Cobra Direct Sale Indonesia in all over 24 provinces that consist of 150 people. Sampling method used in this study using census. The analysis method used is descriptive analysis and Structural Equation Modeling (SEM). The results of the study show that transformational leadership, organizational culture and work motivation influence organizational citizenship behavior. Transformational leadership and work motivation give influence to managerial performance of PT. Cobra Direct Sale Indonesia, while organizational culture has no effect. Organizational citizenship behavior gives influence to managerial performance of PT. Cobra Direct Sale Indonesia. Transformational leadership, organizational culture and work motivation have an effect on managerial performance through organizational citizenship behavior in PT. Cobra Direct Sale Indonesia.